The Utilization of Video-Based Learning in Teaching English for Non-English Major Students - Nurul Hidjrah Hairuddin; Multazam Abubakar; Zul Astri (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2022)
The aim of this study is to investigate students from non-major English department perspectives toward the use of Video-Based Learning in an online English language process. This study was conducted at Politeknik Negeri Ujung Pandang using a convergent-parallel design, a combination of quantitative and qualitative methods. Eighty students of the first semester from the accounting department who were involved in a video-based learning process became the participants of this study. The data was gathered through the use of a questionnaire that included closed-ended and open-ended questions. The data from the closed-ended questions were quantitatively analyzed using descriptive statistics in SPSS. Additionally, a narrative method was used to analyze the open-ended questions. The results of this study indicate that the non-English major students have a positive perspective toward video-based learning utilization because it increases their motivation to learn and makes it easier for them to comprehend the material. Keywords: Video-Based Learning, Non-English Major Students’ Perspectives, Online Class